Woody cover and birds - Loftie-Eaton, Megan (Department of Biological Sciences, 2019)
Major influences on biodiversity in general and on species distributions in particular have occurred on South African landscapes over time as a result of human activities and climate change. Landscapes in southern Africa are not only a product of changes in climate, but they are also a product of the changes brought about by people and their land management practices. In recent decades, bush encroachment has increased dramatically throughout the Savanna Biome of South Africa. Bush encroachment is a vegetation dynamic of global interest. It refers to the thickening or increase of woody vegetation (trees and shrubs) at the expense of grasses and/or herbaceous vegetation. In many areas across South Africa, systems that were once open grassland have become dense thickets dominated by trees and shrubs. Bush encroachment is driven by global factors like increasing carbon dioxide (CO2) levels in the atmosphere as well as local factors like grazing pressures and fire management practices. In Africa, it has long been recognized that there is an influence of vegetation patterns and structure on the distribution and abundance of birds. Changes in habitats due to an increase or decrease in woody cover has been linked to changes in bird diversity and community structure. This thesis looks at what impacts bush encroachment has had on bird distributions in eastern South Africa, with a special focus on the Kruger National Park as well as Palearctic migrants. Chapter 2 of the thesis develops a new quantitative method to relate bird distributions to woody cover. The algorithm is experimental, and an important aspect of the chapter is to investigate whether the results obtained coincide with expectations. The approach first estimates the proportion of the bird species in an area which occur in each woody cover category in a region. It also calculates the proportion of the area of the region which is in each woody cover category. It then uses Jacobs Index to provide an estimate of the extent of preference/avoidance of each species for each woody cover category, on a scale that runs from +1 (the entire population of the species is in that woody cover category) to –1 (none of the population of the species is in that woody cover category). The method is tested on a region consisting of three one-degree grid cells spanning Mpumalanga, Limpopo and Gauteng which include a diversity of woody cover categories, from grassland (no woody cover) to savanna to dense woodland. Chapter 3 applies this approach to the birds of the Kruger National Park, examining which species have distributions which can, and which cannot, be explained to a greater or lesser extent by a preference for a particular range of woody covers. Bird species are selected for close monitoring for ecological management purposes of the Kruger National Park. Chapter 4 considers a set of 10 bird species, all of which are migrants to South Africa from Eurasia, and occur to a large extent during their non-breeding period within the savanna biome of South Africa. For each species, the extent of increase in relative abundance between the first and second bird atlas projects in the region (SABAP1 and SABAP2) is estimated. In most cases, the change of relative abundance can be explained in terms of bush encroachment. The likely provenance of these species in Eurasia is considered; for most species, this area lies in southwestern Asia, i.e. the Ukraine and adjacent Russia. Changes in habitat in this region are also considered and help to improve the understanding of how the populations in South Africa have changed.